Empirical Study on Recycling Used Paper Boxes from Online Shopping in China (Global Business Management Review (GBMR), 2021)
Online shopping is the most popular transaction, where the estimated transaction online is approximately USD 1.9 Trillion with an average growth from 8 -12% every year. Online shopping leads to huge consumption of paper boxes. Since, when the buyers receive the goods, they normally destroyed the paper boxes, throwing them away into a dust bin, and some were kept for nothing. Those papers wasted cause environmental impacts, huge organizational costs,and unnecessary spaces are wasted. The study investigates on activities of returning the used paper boxes through online shopping among university students in China by underpinning the Theory of Reasoned Action (TRA). The survey was conducted among 24 public universities in Guangxi, China, with 401 questionnaires accepted for analysis. The study employed regression analysis to test the hypotheses. Both independent variables have a significant relationship to return the paper wasted boxes from online shopping. This paper has its methodology contribution since a rare study focuses on all the bachelor degree students in public universities in Guangxi, China.